2015
DOI: 10.1186/s12929-015-0166-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin-polyplex-mediated brain-derived neurotrophic factor gene delivery into nigral dopamine neurons prevents nigrostriatal degeneration in a rat model of early Parkinson’s disease

Abstract: BackgroundThe neurotrophin Brain-Derived Neurotrophic Factor (BDNF) influences nigral dopaminergic neurons via autocrine and paracrine mechanisms. The reduction of BDNF expression in Parkinson’s disease substantia nigra (SN) might contribute to the death of dopaminergic neurons because inhibiting BDNF expression in the SN causes parkinsonism in the rat. This study aimed to demonstrate that increasing BDNF expression in dopaminergic neurons of rats with one week of 6-hydroxydopamine lesion recovers from parkins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 73 publications
(115 reference statements)
2
55
0
Order By: Relevance
“…It was also shown that the BDNF administration recovers spontaneous motor behavior in the rat model of PD [95]. Combined treatment with a D3 receptor agonist and BDNF in 6-OHDA lesioned rats led to the stabilization of gait parameters, accelerated recovery of motor coordination and balance, and full recovery from muscle rigidity [96].…”
Section: Study In Pd Animal Modelsmentioning
confidence: 97%
See 3 more Smart Citations
“…It was also shown that the BDNF administration recovers spontaneous motor behavior in the rat model of PD [95]. Combined treatment with a D3 receptor agonist and BDNF in 6-OHDA lesioned rats led to the stabilization of gait parameters, accelerated recovery of motor coordination and balance, and full recovery from muscle rigidity [96].…”
Section: Study In Pd Animal Modelsmentioning
confidence: 97%
“…In the animal models of PD, BDNF brain content was augmented through direct injection of BDNF [88,89], gene transduction by viral vectors [90][91][92][93][94], or delivery via nonviral carriers [95,96] and also via secretion from genetically engineered cells [97][98][99][100][101]. The effects of BDNF treatment were studied in two research schemes in which BDNF was administered before and after the induction of PD.…”
Section: Study In Pd Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…BDNF is a nerve growth factor produced in different regions in the brain with the highest levels in the hippocampus and cerebral cortex and is essential for neuronal function and survival throughout life (Nagahara and Tuszynski, 2011;Zuccato and Cattaneo, 2009). BDNF is considered as a key target for drug development in neurodegenerative diseases (The BDNF StudyGroup, 1999;Hernandez-Chan et al, 2015;Levivier et al, 1995;Lu et al, 2013;Nagahara et al, 2009;Shruthi et al, 2017;Silva et al, 2015). Intraventricular delivery (Beck et al, 1994;Schäbitz et al, 1997) and intravenous bolus (Müller et al, 2008;Schäbitz et al, 2000Schäbitz et al, , 2007 of BDNF, has been shown to be protective in cerebral ischemia in rat, whereas blockade of endogenous BDNF activity was reported to intensify cerebral ischemia (Larsson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%